CULTURAL ECOSYSTEM SERVICES PROVIDED BY PROTECTED FORESTS FOR URBAN FORESTRY - Duman, Beste; Atmiş, Erdoğan (Bartın Üniversitesi, 2018)
The protection forest concept was first mentioned on the forestry legislation in 1924. But, the first protection forest, Belgrad Protection Forest, has been established in the 1950s. There are 55 protection forests in Turkey's different geographical regions. These forests have different functions such as the positive effects on the water cycle, the protection of soil and soil fertility, and the positive effects on the health, climate and carbon cycle, except for the production of wood raw materials. Protection forests have unfortunately lost their importance today. The protection forests have been transformed into areas used for non-forestry benefits, mostly for commercial water production, mining, etc., except for social purposes. However, there is a need for a new understanding that is governed by urban forestry and green infrastructure concepts that will manage the protection forests to meet the needs of the rapidly growing urban population. In this study, one of the important tools of urban forestry management in Turkey with protection forests, cultural ecosystem services it provides to urban forestry and green infrastructure, the selected 10 sample protection forest has attempted to identify. In the selection of the samples protection forests, attention was paid to represent each of the criteria for permanent and temporary protection forest. According to the findings of the study, protection forests offer important cultural ecosystem services to the society by contributing to the environment and human health, strengthening the social ties and establishing the ties between man and nature. The establishment purposes of examined protected forest and the ecosystem services they provide are:- Positively affecting the health of cities and the environment,- Serving the development of the area in terms of tourism through protection of natural of life,- Keeping the housing development and industrialization under control,- Protecting the forests more effectively and preventing the environmental pollution,- Contributing to the protection of water basins by preventing the pollution and clogging of lakes, which are the source of drinking water for the cities,- Offering the public recreation service,- Being an area for research and training for the Faculty of Forestry,- Preventing the clogging of beaches, rivers, railways, and highways by erosion. Considering that the protection forests are an important tool for urban forestry and green infrastructure applications, studies should be carried out to develop a management approach that will manage the protection forests according to their real establishment objectives and to diversify the ecosystem services it provides.

Muhafaza ormanları 1950'li yılların başından itibaren büyük ümitlerle kurulmaya başlanmıştır. Türkiye'nin farklı coğrafi bölgelerinde yer alan toplam 55 muhafaza ormanı bulunmaktadır. Bu ormanlar odun hammaddesi üretimi dışında su döngüsü üzerindeki olumlu etkileri, toprağı ve toprak verimliliğini koruması, sağlık, iklim ve karbon döngüsü üzerindeki olumlu etkileri gibi değişik fonksiyonlara sahiptirler. Ancak muhafaza ormanları günümüzde eski önemini kaybetmiş ve toplumsal amaçlar dışında, daha çok ticari su üretimi, madencilik, vb. ormancılık dışı faydalanmalar için kullanılan alanlar haline dönüşmüştür. Oysa muhafaza ormanlarını hızla artmakta olan kent nüfusunun ihtiyaçlarını karşılamak üzere yönetecek, kent ormancılığı ve yeşil altyapı kavramlarıyla yoğrulmuş yeni bir anlayışa ihtiyaç vardır.  Bu çalışmada, kent ormancılığı yönetiminin önemli araçlarından biri olan muhafaza ormanlarının, kent ormancılığına ve yeşil altyapıya sağladığı kültürel ekosistem hizmetleri, seçilen 10 muhafaza ormanı özelinde belirlenmeye çalışılmıştır. Araştırmanın bulgularına göre; muhafaza ormanları çevreye ve insan sağlığına katkı yaparak, toplumsal bağların kuvvetlendirerek, insan ile doğa arasındaki bağları tesis ederek topluma önemli kültürel ekosistem hizmetleri sunmaktadır.
MUHAFAZA ORMANLARININ KENT ORMANCILIĞINA SAĞLADIĞI KÜLTÜREL EKOSİSTEM HİZMETLERİ
Keywords: Forest Industry Engineering; Orman Endüstri Mühendisliği